IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI BADUNG NO. 5 TAHUN 2016 TENTANG STANDARISASI USAHA VILA DI KABUPATEN BADUNG - Sintia Dewi, A.A. Riska; Supriliyani, Ni Wayan; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTRACT Standards that have been set by the Badung Regency Government is a control of development by having legal certainty. The purpose of this research to find out how the policy implementation from the government is related to the Implementation of Badung Regent Regulations Policy No. 5 of 2016 concerning the Standardization of Villa Business in Badung Regency, so that villa business actors can find out and follow all the requirements and permits that apply. Using the theory of policy implementation according to Charles O. Jones includes organization,,interpretation,and application..This research uses descriptive-qualitative methode with data collection technic in the form of observation,,interviews and documentation..The results of this study are policies on Standardization of Villa Business in Badung Regency that have not been implemented optimally, where in organizational indicators, interpretations, and applications there are still some obstacles, both from the government and from the community. Keywords : Implementation, Business License, Tourism Accomodation